THE CORRELATION BETWEEN BULLYING AND ADOLESCENT SELF CONCEPT JUNIOR HIGH SCHOOL OF GARUT - Rilla, Eldessa Vava (Universitas Tanjungpura, 2019)
The rise of bullying behavior in the junior high school becomes a problem for teenagers during school activity. Again, bullying among teenagers can be bad for victims, perepetrators or witnesses. It can develop self from in adolescents. The purpose of this research was to know the relationship of bullying and self concept in SMP Negeri 5 Garut. This was a descriptive analytic study with cross sectional method. The number of respondents were 105 students class VII dan VIII. Data collection was done by using self administred questionare. The results showed that most teenagers in the SMP Negeri 5 Garut experienced bullying 53% and the majority of teenagers in the SMP Negeri 5 Garut has a positive self-concept 57%. The results releaved that there was significant correlation between bullying and adolescent self concept (p = 0,020) which means there is a significant relationship between bullying with adolescent self-concept. In conclusion the teacher must provide knowledge about bullying and supervise the students to avoid bullying that will result in student self concept.